PELESTARIAN LINGKUNGAN DALAM PERPEKSTIF AL-QUR’AN: STUDI QUR’AN TEMATIK - Muhamad Adji Saputra; Muhammad Alif (CV. Adiba Aisha Amira, 2025)
The ecological crisis faced by humanity today reflects a moral and spiritual failure in preserving nature. The main objective of this study is to examine environmental preservation from the perspective of the Qur'an using a thematic interpretation approach (tafsir maudhu'i). Through the exploration of verses related to nature, this study identifies a number of key concepts such as amanah (trust), khalifah (human leadership), mizan (balance), and the prohibition of facade (damage). The Qur'an firmly positions humans as guardians of the earth who carry ethical and religious responsibilities for preserving nature. The findings of this study reveal that caring for nature is not merely an ethical obligation, but also part of worship and a form of devotion to God. The resulting Qur'anic ecological ethics can be used as a normative basis for the development of environmental education, da'wah activities, and the formulation of public policies based on Islamic values. This study also emphasizes the importance of integrating the values of revelation in facing global environmental challenges wisely and sustainably